CYP2C9*2 Allele Increases Risk for Hypoglycemia in POR*1/*1 Type 2 Diabetic Patients Treated with Sulfonylureas - Ragia, G.; Tavridou, A.; Elens, L.; Van Schaik, R. H. N.; Manolopoulos, V. G. (Experimental and Clinical Endocrinology & Diabetes, 2014)
It is previously shown that carriers of the defective allele CYP2C9*3 that leads to impaired sulfonylurea metabolism are at increased sulfonylurea-induced hypoglycemia risk due to diminished drug metabolism, whereas no effect of CYP2C9*2 allele was found. Recently, a polymorphism in P450 oxidoreductase (POR) gene, assigned as POR*28 allele, was associated with increased CYP2C9 activity. The aim of this study was to assess i) the effect of POR*28 allele on sulfonylurea-induced hypoglycemia risk and ii) the association of CYP2C9*2 allele with hypoglycemia risk in non-carriers of POR*28 allele. The study group consisted of 176 patients with diagnosed type 2 diabetes mellitus (T2DM) treated with sulfonylureas, of whom 92 patients had experienced at least one drug-associated hypoglycemic event (cases), while 84 had never experienced a hypoglycemic event (controls). POR*28 allele was detected by use of real-time TaqMan PCR. POR*28 allele was not associated with sulfonylurea-induced hypoglycemia. In POR*1/*1 patients, CYP2C9*1/*2 genotype was more common in cases than in controls (32.7 vs. 14.3%, p=0.041). In a model adjusted for age, BMI, duration of T2DM and renal function, and POR*1/*1 entered as a selection variable, CYP2C9*2 allele increased the hypoglycemia risk in response to sulfonylurea (odds ratio: 3.218, p=0.031). In conclusion, our results suggest that POR*28 allele is masking the association of CYP2C9*2 allele with sulfonylurea-induced hypoglycemia. Therefore, POR*28 allele is an important source of CYP2C9 activity variability and combined with CYP2C9 gene polymorphisms may explain individual variability in the effect of sulfonylureas.
Keywords: sulfonylurea; hypoglycemia; pharmacogenetics; POR*28; CYP2C9*2